(untitled) (Bangladesh Journal of Medical Science, 2013)
Introduction: Low bone mass is a serious complication of post menopausal women with rheumatoid arthritis. We determined the Change in Bone Mineral Density in postmenopausal women with rheumatoid arthritis. Methods: This retrospective cohort study was carried out on consecutive postmenopausal women with rheumatoid arthritis who were referred to the Azar 5th teaching hospital affiliated to Golestan University of Medical Sciences, North of Iran in 2009. The required data were gathered from the patients medical records. The data were analyzed using SPSS software and statistical tests. Results: We studied 98 postmenopausal women with rheumatoid arthritis. Mean number of years since menopause and mean duration of disease were 9.39 and 5.13 respectively. T Score mean in femoral neck and lumbar spines was -1.45±1.26 and -2.45±1.44 respectively. The overall prevalence of osteoporosis at both the lumbar spine and femoral neck was 13.3. We have found a significant correlation between age, duration of disease, duration of menopause and bone mineral density (P-Value<0.01). Conlusion: Our results indicate a negative effect of age, number of years since menopause and duration of disease on bone mineral density. So, BMD should be measured in high risk women prior to the implementation of any treatment or prevention program. Bangladesh Journal of Medical Science Vol. 12 No. 02 April13 Page 158-163 DOI: http://dx.doi.org/10.3329/bjms.v12i2.14944